Cover Picture: Iodide‐Catalyzed Ring‐Opening Cyclization of Cyclohexane‐1, 3‐dione‐2‐spirocyclopropanes (Adv. Synth. Catal. 15/2018). Issue 15 (25th July 2018) - Nambu, Hisanori; Onuki, Yuta; Ono, Naoki; Yakura, Takayuki
Abstract : Theinside cover picture, provided by Hisanori Nambu and Takayuki Yakura, illustrates the regioselective ring‐opening of spirocyclopropanes with iodide catalysts followed by cyclization, affording tetrahydrobenzofuran‐4‐ones in high yields. The iodide ion acts as a good nucleophile to open the cyclopropane and as a good leaving group to trigger the cyclization that leads to the dihydrofuran. Details of this work can be found in the update on pages 2938–2944 (H. Nambu, Y. Onuki, N. Ono, T. Yakura, Adv. Synth. Catal .2018, 360, 2938–2944; DOI:10.1002/adsc.201800551 ).